2011
DOI: 10.1021/ie201273n
|View full text |Cite
|
Sign up to set email alerts
|

Step Changes and Deactivation Behavior in the Continuous Decarboxylation of Stearic Acid

Abstract: Deoxygenation of dilute and concentrated stearic acid over 2% Pd/C beads was performed in a continuous reactor at 300 °C and 20 bar pressure of Ar or 5% H2/Ar. Stable operation was obtained in 5% H2 atmosphere, with 95% conversion of 10 mol % dilute stearic acid in dodecane and 12% conversion of pure stearic acid. Deactivation took place in H2-deficient gas atmosphere, probably as a result of the formation of unsaturated products and coking in the pore system. Transient experiments with step changes were perfo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
33
0
1

Year Published

2013
2013
2018
2018

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 45 publications
(34 citation statements)
references
References 43 publications
0
33
0
1
Order By: Relevance
“…Mature understandings on the influences of specific process conditions are yet to be established in view of the complex reactions involved. However, some recent works reported managed to shed some light on this area [48,50,60].…”
Section: Factors Influencing the Deoxygenation Processmentioning
confidence: 99%
See 3 more Smart Citations
“…Mature understandings on the influences of specific process conditions are yet to be established in view of the complex reactions involved. However, some recent works reported managed to shed some light on this area [48,50,60].…”
Section: Factors Influencing the Deoxygenation Processmentioning
confidence: 99%
“…Pd, Pt and Ni on γ-Al 2 O 3 have been investigated for deoxygenation of waste fat containing a mixture of oleic acid and tripalmitin in the presence of solvent under hydrogen atmosphere. It has been observed that Pd/γ-Al 2 O 3 catalyst is more active than the Pt/γ-Al 2 O 3 catalyst and also more selective for production of the C17 and C15 diesel-like hydrocarbons [60]. The higher activity was due to the higher content of active metal (Pd) in the Pd/γ-Al 2 O 3 catalyst than the active metal (Pt) in the Pt/γ-Al 2 O 3 catalyst.…”
Section: Supported Metal Catalyst Typementioning
confidence: 99%
See 2 more Smart Citations
“…It could also be produced through water gasshift reaction and methanation [28,29] in which molecules of H 2 from dehydrogenation reactions react with molecules of other gaseous products, i.e., CO 2 and CO (by-products from decarboxylation and decarbonylation), as given in the following reactions;…”
Section: Reusability Study Of Nimcf Catalystmentioning
confidence: 99%